KAJIAN PRODUK WISATA BAHARI PANTAI TANJUNG BENOA - Made Arya Astina; Ketut Muliadiasa (Institut Pariwisata dan Bisnis Internasional, 2018)
This study aims to identify the quality of marine tourism products which are limited to indicators of Attractions, Accessibility, Amenities, and Ancilary on Tanjung Benoa marine tourism destinations, knowing the socio-demographic conditions of tourists who come to Tanjung Benoa marine tourism destinations, as well as contributing marine tourism development strategies in Tanjung Benoa. Based on the purpose of this study, several theories, concepts and literature studies referred to this study include the concept of tourism, marine tourism, product quality (tourist attraction), product development. Meanwhile, the research method that used in this study was descriptive analysis about the conditions of Attractions, Accessibility, Amenities, and Ancilary in marine tourism on the Tanjung Benoa beach. Direct observation and distribution of questionnaire for the tourists in the Tanjung Benoa area was carried out to directly assess the object of research at this location. The analysis of secondary data consist of the number and condition of facilities and infrastructure assessed from the perception of tourists. As the result of the problem formulation in this study, it could be obtained the data or information about the condition of attraction quality, amenities and activities in Tanjung Tanjung Benoa marine tourism, and contributes to the development strategy of the tourism area. The results of this study could be used to develop marine tourism in the Tanjung Benoa tourist area which is expected to be a quality and sustainable marine tourism area.Â Keywords: Marine Tourism, Quality of tourist attraction, Development potential